PENGUKURAN RISIKO PADA RETENSI OPTIMAL UNTUK REASURANSI STOP LOSS DENGAN VALUE AT RISK - Sunarwatiningsih, Agustina; Wilandari, Yuciana; Rusgiyono, Agus (MEDIA STATISTIKA, 2011)
Reinsurance is an effective risk management tool for an insurer to minimize the risk of loss. Optimization criteria is based in a minimum VaR of the total risk of in insurer, to derive the optimal retention in stop loss reinsurance. The resulting optimal solution of optimization criterion has several important characteristics, such as: the optimal retention has a very simple analytic form; the optimal retention depends only on the assumed loss distribution and the reinsurer’s loading factor; if optimal solution exist, then VaR based optimization criteria yield the same optimal retentions; there exist a exceeds risk tolerance level which the insurer optimally should not reinsure her risks. The approach allows us to obtain different results of the optimization problem depends on the measurement of risk used. Furthermore, with optimal retention of risk measurement and minimum of VaR to the total risk, the companies be able to minimize or reduce the loss ratio of claims own retention ceding company. One way to show the existence of an optimal retention used survival function distribution exponensial. Key words: Stop Loss Reinsurance, Optimal Retention, Value at Risk (VaR)